Insights Into the Role of Mesothelin as a Diagnostic and Therapeutic Target in Ovarian Carcinoma - Shen, Jiayu; Sun, Xiwen; Zhou, Jianwei (Frontiers in Oncology, 2020)
Ovarian malignancies remain the leading cause of death in female gynecological tumors. More than 70% patients are diagnosed with advanced stage with extensive metastatic lesions in abdominal cavity due to lack of symptoms in early stage and sensitive diagnostic approaches. Mesothelin, a glycosylphosphatidylinositol-anchored membrane glycoprotein, participates in cell adhesion, tumor progression, metastasis, and drug resistance. Anyhow, the mechanism is still poorly understood. The differential expression pattern of mesothelin in normal and cancer tissues advocated it a promising target for diagnosis and therapeutic applications. Several clinical trials are underway to evaluate the safety and efficacy of mesothelin-targeted drugs, including CAR T cells, immunotoxin, antibody-drug conjugates, and vaccine. This review is aimed to briefly discuss the characteristics of mesothelin and the latest progress in mesothelin targeting therapies.